A Critique on the Book Fusus al-Hakam and The School of Ibn Arabi - Parisa Goudarzi; Zahra Jebraeilzade (پژوهش‌نامۀ انتقادی متون و برنامه‌های علوم انسانی)
Fusus al-Hakam is written by Muhyiddin Ibn Arabi. During the nearly eight centuries since this work was written, many writers have tried to unravel its knots with their descriptions and interpretations. The book Fusus al-Hakam and The School of Ibn Arabi by Abu al-'Ala Afifi is one of the most recent commentaries on Fusus al-Hakam, which was scrutinized in the form of commentaries. In this article, we try to introduce and critique this book translated by Mohammad Javad Gohari. The present book has been written as a "commentary" on Fusus al-Hakam; therefore, not all expressions of Fusus have been studied by the author. In the present book, Afifi has tried to explain in a language understandable regarding the mystical and philosophical issues of Fusus and to solve some linguistic and intellectual difficulties of Ibn Arabi for the western readers who are less familiar with the issues of unity. Therefore, this book can be helpful in understanding the complex issues of Fusus al-Hakam. Another prominent point of this book is the author's lack of prejudice against Ibn Arabi, which has turned him into a fair critic and impartial judge in the evaluation of Fusus. The author also tries to help to better establish them in the mind of the reader by emphasizing and repeating the key topics of Ibn Arabi's view in the book, including the unity of existence, the relationship between the universe and God, and related topics.